THE RELATIONSHIP BETWEEN SYNTACTIC AND SEMANTIC: A STUDY OF LINGUISTIC TYPOLOGY - Soares, Antonio (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2019)
This research entitled “The Relationship between Syntactic and Semantic : A Study of Linguistic Typology.” is intended to give a clear descriptions related to the relationship between syntactic and semantic on some languages. This research was focused on some clause structures typologycally either syntactically or semantically. The scope of this research was more focused on the transitive verbs to have more descriptions related to the relationship between syntactic and semantic to find out whether a clause structure on syntactic can be accepted or cannot be accepted semantically. The theory of linguistics typology was applied in this research because the principle of linguistics typpology is to find out the similarities and the differences among all the type of languages universally. The introspective reflexive and the descriptive method were applied to gain the data in this research and the qualitative descriptive method was applied to analyse the data.